2012
DOI: 10.1007/978-1-61779-953-2_15
|View full text |Cite
|
Sign up to set email alerts
|

Labeling and Imaging Mesenchymal Stem Cells with Quantum Dots

Abstract: Mesenchymal stem cells (MSCs) are multipotent cells with the potential to differentiate into bone, -cartilage, adipose, and muscle cells. Adult derived MSCs are being actively investigated because of their potential to be utilized for therapeutic cell-based transplantation. Methods to track MSCs in vivo are -limited, preventing long-term functional studies of transplanted cells. Quantum Dots (QDs) offer an alternative to organic dyes and fluorescent proteins to label and track cells in vitro and in vivo. Nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…In contrast, MSCs can also be directly labelled with nanoparticles such as GNPs. Other examples include superparamagnetic iron oxide nanoparticles and quantum dots, in which the former is detectable by MRI [38], while the latter is a fluorescence-based technique [39]. …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, MSCs can also be directly labelled with nanoparticles such as GNPs. Other examples include superparamagnetic iron oxide nanoparticles and quantum dots, in which the former is detectable by MRI [38], while the latter is a fluorescence-based technique [39]. …”
Section: Discussionmentioning
confidence: 99%
“…These comprise atoms for releasing electrons and cadmium as one of the chemicals. Most of their usage is limited to tracking stem cells undergoing differentiation and migration [75, 76]. These are photostable and have longer longevity.…”
Section: Influence Of the Biophysical Microenvironment On Stem Cell Rmentioning
confidence: 99%
“…Another product frequently used for stem cell labelling is quantum dots (QDs; Wang, Xu, & Ow, ). QDs are fluorescent nanoparticles, which are resistant to metabolic degradation (Collins, Gunst, Cascio, Kypson, & Muller‐Borer, ), have minimal cytotoxic effects, and have been shown not to interfere with proliferation of rat bone marrow MSCs in culture (Muller‐Borer, Collins, Gunst, Cascio, & Kypson, ). Visualization of QDs in labelled rat MSCs is possible in cardiomyocyte cocultures for up to 7 days (Muller‐Borer et al, ), and QDs have been demonstrated to be present in canine hearts 8 weeks following delivery of QD‐labelled human MSCs (Rosen, Kelly, Schuldt, et al, ).…”
Section: Introductionmentioning
confidence: 99%